PENGARUH STRUKTUR DAN PROSES SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA INSTALASI RAWAT INAP PADA RUMAH SAKIT UMUM PROVINSI (RSUP) NUSA TENGGARA BARAT - Purnama, Asri; fullah, Syae (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Along with the increasing demand for health services and the emergence of a growing number of hospital, the public hospital of province (RSUP) NTB Hospital should be able to operate effectively and efficiently in order to compate with other hospitals. Management control system is necessary for hospitals to guide and motivate businesses to achieve organizational goals. This study aims to find out the influence of independent variables namely the structure and proces management control system to the dependent variable is the installation performance inpatient. Analysis tools used in this study is multiple regression. Based on the results of t-test (partial) and F test (simultaneous) showed that the independent variable, structure of management control system and process control management system has a significant influence on the dependent variable installation performance inpatient. The results of multiple linear regression analysis to obtain the structure of management control system p value = 0,032 and for process control management system available p value = 0,000 Adjusted R Square value is 0,790 indicate that dependent variable is able to described by independent variable as 79,0%, while remain is 21% is described as by other factor that is not included in this model. Suggestion that able recommended related to this research is that the management of hospital RSUP NTB can sustain the structure and process of management control system to support performance inpatient installation. Key words : Structure, Process, System, Control, Management, Management Control System , Performance